Application of Portfolio-based Learning Model on Islamic Education Subjects in SMP Negeri 2 Percut Sei Tuan - Nuraini Nuraini (UMSU, 2022)
This study aims to determine how the application of portfolio-based learning models in Islamic religious education subjects at SMP Negeri 2 Percut Sei Tuan. This research was obtained on the assumption that the application of a portfolio-based learning model at SMP Negeri 2 Percut Sei Tuan went well and was able to make students enthusiastic about learning Islamic Religious Education subjects. This research method uses qualitative research, with the type of case study research. Data collection techniques used in this study were observation, interviews and documentation. While the data analysis in this study used ethnographic analysis of James. P Spradley. The data validity technique uses the technique according to Lincoln and Guba in Moleong. Based on the results of research and data analysis, it can be concluded that the application of portfolio-based learning models in Islamic Religious Education subjects has been running well and is able to increase students' interest in learning.